2008
DOI: 10.1007/s11103-008-9377-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversed end Ds element: a novel tool for chromosome engineering in Arabidopsis

Abstract: The maize Ac/Ds transposable element (TE) transposes by a "cut and paste" mechanism. Previous studies in maize showed that when the TE ends are in reversed orientation with respect to each other, alternative transposition reactions can occur resulting in large scale genome rearrangements including deletions and inversions. To test whether similar genome rearrangements can also occur in other plants, we studied the efficacy of such alternative transposition-mediated genome rearrangements in Arabidopsis. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Previous research has identified examples of "fused ends"; i.e., cases in which the ITS is deleted and the 59 and 39 Ac/Ds termini are ligated together (Gorbunova and Levy 1997;Krishnaswamy et al 2008). The presence of fused ends among the mutant alleles tested here could be detected by PCR with Ac 59 end primer (Ac120r) and Ac 39 end primer (Ac4436f) ( Table 2).…”
Section: A Translocations and Large Inversions (Five Cases)mentioning
confidence: 73%
“…Previous research has identified examples of "fused ends"; i.e., cases in which the ITS is deleted and the 59 and 39 Ac/Ds termini are ligated together (Gorbunova and Levy 1997;Krishnaswamy et al 2008). The presence of fused ends among the mutant alleles tested here could be detected by PCR with Ac 59 end primer (Ac120r) and Ac 39 end primer (Ac4436f) ( Table 2).…”
Section: A Translocations and Large Inversions (Five Cases)mentioning
confidence: 73%
“…(Dooner and Weil 2007;Huang and Dooner 2008). Another study has shown that chromosomal rearrangements including deletion, inversion, and somatic translocation can also arise through transposition reactions involving Ds elements in Arabidopsis (Krishnaswamy et al 2008). In all of these cases, the rearrangement junctions have been precise or nearly so.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, chromosomal aberrations induced by the Ac/Ds system were initially identified by loss of kernel pericarp or aleurone pigmentation specified by the p1 and bz1 genes, respectively (5,7,9). In Arabidopsis and rice, candidate rearrangement events were detected through loss of selectable marker genes included in the Ds- containing transgene construct (39; C. Yu et al . 2011, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%